DEVELOPMENT OF A COUNSELING POCKET BOOK FOR PREVENTING DRUGS AT ADHYAKSA HIGH SCHOOL JAMBI CITY - Shilvianty, Sheena (Jurnal Kopendik, 2022)
This study aims to develop a pocket book of guidance and counseling that can be used for the prevention of the dangers of drugs, research on the use of the ADDIE model, consists of five main stages, namely Analysis, Design, Development, Implementation, and Evaluation. linguists, and guidance and counseling experts. Based on the development of guidance and counseling books for the prevention of the dangers of drugs at Adyaksa High School Jambi City, it is very effective for students' knowledge and can increase students' knowledge about preventing drugs with a t value of 6.119 > 0.3550 which means that guidance and counseling books are significant for preventing the dangers of drugs at Adyaksa City High School. Jambi. The assessment by the material expert obtained an average of 3 which was included in the very feasible category, the assessment by the media expert was obtained in the very feasible category.